Whispered speech recognition using deep denoising autoencoder - Grozdić, Đorđe T.; Jovičić, Slobodan T.; Subotić, Miško (Engineering applications of artificial intelligence, 2017)
Recently Deep Denoising Autoencoders (DDAE) have shown state-of-the-art performance on various machine learning tasks. In this paper, the authors extended this approach to whispered speech recognition which is one of the most challenging problems in Automatic Speech Recognition (ASR). Namely, due to the profound differences between acoustic characteristics of neutral and whispered speech, the performance of traditional ASR systems trained on neutral speech degrades significantly when whisper is applied. This mismatch between training and testing is successfully alleviated with the new proposed system based on deep learning, where DDAE is applied for generating whisper-robust cepstral features. This system was tested and compared in terms of word recognition accuracy with conventional Hidden Markov Model (HMM) speech recognizer in an isolated word recognition task with a real database of whispered speech (WhiSpe). Three types of cepstral coefficients were used in the experiments: MFCC (Mel-Frequency Cepstral Coefficients), TECC (Teager-Energy Cepstral Coefficients) and TEMFCC (Teager-based Mel-Frequency Cepstral Coefficients). The experimental results showed that the proposed system significantly improves whisper recognition accuracy and outperforms traditional HMM-MFCC baseline, resulting in an absolute 31% improvement of whisper recognition accuracy. The highest word recognition rate of 92.81% in whispered speech was achieved with TECC feature.